2016
DOI: 10.1063/1.4942509
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electron mobility in epitaxial (Ba,La)SnO3 films on BaSnO3(001) substrates

Abstract: We report the growth of Ba1−xLaxSnO3 (x = 0.00, 0.005, 0.01, 0.02, and 0.04) thin films on the insulating BaSnO3(001) substrate by pulsed laser deposition. The insulating BaSnO3 substrates were grown by the Cu2O-CuO flux, in which the molar fraction of KClO4 was systematically increased to reduce electron carriers and thus induce a doping induced metal-insulator transition, exhibiting a resistivity increase from ∼10−3 to ∼1012 Ω cm at room temperature. We find that all the Ba1−xLaxSnO3 films are epitaxial, sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(41 citation statements)
references
References 35 publications
0
41
0
Order By: Relevance
“…Note that careful control of the p(O 2 ) is essential for achieving simultaneous increases in the structural and electrical properties, which can explain the further improvement in the RT μ e at the small expense of point defect generation by precise p(O 2 ) control Fig. 4 Comparison of the room temperature electron mobility vs. carrier concentration for our optimized LBSO films wet 0.5% H 2 -annealed at 950°C (red stars) and previously reported LBSO films, i.e., PLD-grown LBSO thin films on an STO substrate 11 (black squares), and on a single-crystal BSO substrate 16 (green circles), MBE-grown LBSO thin films on an STO substrate 13 (blue triangles, orange diamonds), and single-crystal LBSO 38 (pink hexagons)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that careful control of the p(O 2 ) is essential for achieving simultaneous increases in the structural and electrical properties, which can explain the further improvement in the RT μ e at the small expense of point defect generation by precise p(O 2 ) control Fig. 4 Comparison of the room temperature electron mobility vs. carrier concentration for our optimized LBSO films wet 0.5% H 2 -annealed at 950°C (red stars) and previously reported LBSO films, i.e., PLD-grown LBSO thin films on an STO substrate 11 (black squares), and on a single-crystal BSO substrate 16 (green circles), MBE-grown LBSO thin films on an STO substrate 13 (blue triangles, orange diamonds), and single-crystal LBSO 38 (pink hexagons)…”
Section: Resultsmentioning
confidence: 99%
“…This low μ e has been attributed to the abundance of TDs 9 that inevitably form during epitaxial growth due to large lattice mismatch with the substrate, e.g., SrTiO 3 or MgO. Therefore, considerable effort has been devoted to decreasing the density of TDs by using substrates with a lattice constant that is similar to or even the same as that of BSO [13][14][15][16] or by inserting buffer layers between BSO epilayers and typical substrates 12,[17][18][19] to release the lattice mismatch strain.…”
Section: Introductionmentioning
confidence: 99%
“…performed ab initio calculations for the structural and electronic properties of KO-and NbO 2 -terminated KNbO 3 (001) surfaces and the results showed that the surface energy for the KO termination is about 1.21 eV, which is larger than that of the NbO 2 termination of 0.75 eV.Until recently, several research groups have used BaSnO 3 (001) material as an insulating substrate for the deposition of metal oxide thin films 15. Ó 2017 The Minerals, Metals & Materials Society…”
mentioning
confidence: 98%
“…Evidence that this effect is often at play in BSO is the observation of different mobility values for films grown via different synthesis routes despite having similar substrates and doping levels792223. Even homoepitaxial films24 show much lower mobility compared to bulk single crystals suggesting an important role of point defects. Furthermore, films grown by MBE show a large variation in the mobility values despite having identical carrier concentration16.…”
mentioning
confidence: 99%